Not All At-Risk Boys Have Bad Outcomes: Predictors of Later Life Success - Craig, Jessica M. (Crime & delinquency, 2020)
Scholars have recently identified protective factors that decrease the effects of risk factors on later offending. Others have investigated how offending risk factors affect other life outcomes, such as employment and health. The current study combined these areas to identify protective factors that predicted life success through mid-adulthood. The Cambridge Study in Delinquent Development was used to identify risk-based and interactive protective factors for later life success among males at risk for poor life success. Across three risk conceptualizations, several protective factors were identified that predicted life success in a variety of domains at age 48. This research indicates that early childhood interventions may not only help reduce future offending but also increase the child's chances of doing well in other life domains.